An investigation into LA-spICP-ToF-MS uses for in situ measurement of environmental multi-elemental nanoparticles. Issue 10 (19th August 2021) - Holbrook, Timothy Ronald; Gallot-Duval, Doriane; Reemtsma, Thorsten; Wagner, Stephan
Abstract : A LA-spICP-ToF-MS method was developed and systematically compared with the traditional neb-spICP-ToF-MS. The method was shown to be of significant use for the measurement of environmental multi-elemental particles extracted from or embedded within a solid sediment. Abstract : Characterization and investigation into complex nano-fraction particle samples have traditionally been done using nebulizer single particle inductively coupled plasma mass spectrometry (neb-spICP-MS). Here a method was developed and tested for the direct analysis of multi-elemental particles (MEPs) in sediment samples using laser ablation (LA-spICP-ToF-MS). A comparison between the neb-spICP-ToF-MS and LA-spICP-ToF-MS was made to determine possible differences and advantages of the techniques using standard AgAu core–shell particles and environmental samples obtained via cloud point extraction procedures of a road runoff sedimentation basin. Using the results obtained by this method comparison, comparison metrics were then used to test the usability of LA-spICP-ToF-MS on unextracted sediment. Three main groups of signals were identified, overly abundant signals which cannot be used for single-particle analysis at the chosen measurement parameters, highly abundant signals that when compared with the two previous methods produced comparable results for elemental ratios and single-particle fingerprinting. Lastly, low abundant well-defined elements such as the platinum group elements (PGEs) were ideally suited for measurement from unextracted sediment. The introduced LA-spICP-ToF-MS is likely suitable for the analysis of MEPs for groups 2 and 3 in sediment samples with minimal sample preparation (sediment homogenization, drying, and distribution of sediment on tape) and capable of MEP source allocation for the reported element groups.